Pengembangan Gim Edukasi Mengenai Narkoba Berbasis Desktop - Muhammad Ahimsa Dhia; Harya Bima Dirgantara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study discusses the development of an educational desktop-based game that addresses narcotics, psychotropics, and addictive substances. This "Kuis Anti Narkoba" game aims to be an interactive medium for learning about drugs. This game was developed using the Game Development Life Cycle (GDLC) methodology, which has 6 stages: initiation, pre-production, production, testing, beta, and release. The result of this research is a game titled "Kuis Anti Narkoba", which according to the results of test that have been conducted, 13 out of 14 people claim to be positive that this application can be an interesting learning medium about drugs and their types.